Looking for Luck in Farming: Intersubjective Relationships in the Mujarobat Manuscript - Supriadi, Dedi (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2022)
This study focuses on the intersubjective relationships contained in the Mujarobat text. This study comes from the still developing local beliefs and traditions of the coastal communities of North Java which are influenced by pre-Islamic beliefs and Islamic beliefs. Among the beliefs that still exist, it is the belief in predictions and calculations to get good luck and avoid bad luck. This study specifically aims to discuss how to grow plants on pages 40, 41, 42, 49, and 50 in the Mujarobat text. This study shows that the Mujarobat text contains local knowledge and intersubjective relationships between humans and humans as well as humans and non-humans—God and nature. Thus, using the paradigm of ancestral religions, this study argues that there is an intersubjective relationship between humans and non-humans that is responsible, ethical, and reciprocal when planting plants in the Mujarobat text which aim to get lucky.